Selected Rand abstracts : a quarterly guide to publications of the RAND corporation - Research and Development Corporation (Santa Monica, Calif. : RAND., 1984)
Includes publications previously listed in the supplements to the Index of selected publications of the Rand Corporation (Oct. 1962-Feb. 1963)
PTSL : v.22 no.4 1984, v.25 no.1 1987, v.26 no.1 1988, v.26 no.2 1988, v.26 no.3 1988, v.26 no.4 1988, v.27 no.1 1989, v.27 no.3 1989, v.27 no.3 1989, v.28 no.1 1990, v. 28 no.2 1990, v.28 no.3 1990, v.28 no.4 1990, v.29 bil.2 1991, v.29 no.3 1991, v.29 no.4 1991, v.30 no.1 1992, v. 31 no. 2 1992, v. 32 no. 2 1994, v. 34 no. 1 1996, v. 34 no. 2 1996, v. 36 Jan - Dec. 1998, v. 37 no.1 1999
Keywords: Abstracts -- Periodicals